Experimental study on hydrothermal characteristics of shell and tube heat exchanger using phase change material-based hybrid nanofluid - Sahoo R.R.; Sarkar J. (My University, 2025)
The shell-and-tube heat exchanger (STHX) is probably the most ubiquitous form of heat exchanger in many industrial settings. In the current investigation, various nanofluids (Al2O3, PCM, CNT, Al2O3+PCM, and Al2O3+CNT) at volume concentrations of 0.01% and 0.1% were used to test the hydrothermal performance in a STHX. This study aimed to investigate the influence of the Nusselt number and friction factor on the Reynolds number and the hydrothermal performance of STHX at various volume fractions. The execution of an experimental investigation accomplished this. The findings demonstrated that the pressure drop and heat transfer coefficient depend on the nanofluid's flow rate, that it is superior to DI water and improves with volume. The hi/∆p value rises for Al2O3 due to pressure drop impacting heat transmission, but it falls for phase change material (PCM) and Al2O3+PCM nanofluids. The hybrid nanofluid Al2O3+CNT flowing at 10lpm in the tube has a 15.60% greater friction factor and an average Nusselt number of 38.08% compared to the base fluid. The heat transfer coefficient, Nusselt number, pressure drop, and friction factor for Al2O3+PCM at 8.33lpm increase by 9.18%, 8.91%, 36.84%, and 5.98%, respectively, with an increase in volume concentration from 0.01 to 0.1%. Nanofluids that are either mono- or hybrid and contain PCM dispersion have a better heat transfer coefficient at low flow rates. The pressure loss increases with increasing flow rate because PCM particles raise dynamic viscosity. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.